(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The present article is devoted to the comparative cognitive and linguocultural analysis of the concept “guest / қонақ” in Russian and Kazakh languages. The relevance of the study is determined by the need to identify both universal and culture-specific features of the conceptualization of hospitality as a fundamental social category that reflects mental attitudes, value orientations, and interpersonal behavioral models in different linguocultures. The purpose of the research is to reveal the cognitive structure and axiological parameters of the concept “guest / қонақ” based on proverbs and phraseological units in Russian and Kazakh. The research objectives include definitional and semantic analysis, frame modeling, and comparative description of linguistic realizations. The methodology is based on cognitive linguistics, linguoculturology, and paremiological analysis. The empirical basis consists of fixed expressions and proverbs containing the lexical component “guest / қонақ”. The study reveals that in the Russian tradition, the concept “guest” bears ambivalent semantics – ranging from a respected visitor to a potential threat, whereas in the Kazakh worldview, “қонақ” is sacralized as a blessed figure symbolizing peace, unity, and social openness. The scientific novelty lies in the systematic linguocultural interpretation of the concept, previously unexplored in an intercultural context. The practical significance of the study lies in its applicability in the teaching of intercultural communication, ethnolinguistics, cultural studies, and translation practice. Keywords: guest / қонақ, concept, paremia, cognitive linguistics, intercultural analysis.